2014
DOI: 10.1186/1556-276x-9-19
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature photoluminescence study of exciton recombination in bulk GaAsBi

Abstract: The exciton recombination processes in a series of elastically strained GaAsBi epilayers are investigated by means of time-integrated and time-resolved photoluminescence at T = 10 K. The bismuth content in the samples was adjusted from 1.16% to 3.83%, as confirmed by high-resolution X-ray diffraction (HR-XRD). The results are well interpreted by carrier trapping and recombination mechanisms involving the Bi-related localized levels. Clear distinction between the localized and delocalized regime was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 19 publications
4
23
0
Order By: Relevance
“…Mazzucato et al (2014), confirming the results found in Ref. Oriaku and Pereira (2017), the initial values for q; r; C ð Þ were 1E15; 2E À 3; 1 ½ .…”
Section: Numerical Methods and Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Mazzucato et al (2014), confirming the results found in Ref. Oriaku and Pereira (2017), the initial values for q; r; C ð Þ were 1E15; 2E À 3; 1 ½ .…”
Section: Numerical Methods and Resultssupporting
confidence: 80%
“…Experimental data such as in Refs. Krier et al (2012) and Mazzucato et al (2014) provides the luminescence peak energy at different temperatures for InAsN. Thus, by applying the least squares method, we can estimate the parameters q; r; C ð Þ so that the residual between the theoretical function and the experimental data is minimized.…”
Section: Numerical Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar PL results were found in GaAsN alloys when the excitation power was increased [41]. Recently, at low temperature, Mazzucato et al [32] have demonstrated clear distinction between the localized and delocalized states in the spectral and temporal photoluminescence emission. Indeed, at low excitation power, the localized emission is more pronounced.…”
Section: Resultssupporting
confidence: 77%
“…Epitaxial layers of GaAsBi have demonstrated a reduced temperature dependence of the lasing wavelength, which makes them promising for the manufacture of laser diodes and semiconductor optical amplifiers that do not require Peltier cooling [10]. Recently, a large number of reports on detailed optical characterizations of GaAsBi were published [7,14,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. They include temperature dependence of PL, time-resolved PL, Photomodulated transmittance and photoreflectance (PR).…”
Section: Introductionmentioning
confidence: 99%